Urban Public Streets in the Collective Memory: A Case Study Of Uray Street In Mersin - Elvan Elif Özdemir (DEPARCH Journal of Design Planning and Aesthetics Research, 2023)
Streets are public spaces that constitute the transportation network of cities, not only as a means of transportation, but also in the spaces they host, which have an important place in the daily life of individuals. It is affected by the social, social and economic transformations and changes we live in, in public spaces, which are an important part of cities, as well as cities. This situation causes the continuity of the urban memory to weaken and even to disappear over time. Collective memory, which has a strong connection with the physical structure of cities and the formation of their identity, is the reading of the signs and symbolic meanings of the physical environment in the cognitive structure of society with social, historical and psychological components. Cities, which are rapidly changing and transforming with new technological and economic advances, are gradually moving away from their own past and losing their identities. With its 'modern' spaces, which are standardized in terms of living spaces and, more accurately, monotonous, the city also destroys and weakens the bond it establishes with its inhabitants. This situation causes the city to lose its memory. This study investigates the changing and transforming position of Uray Street, which has been an important street since the first establishment of Mersin, a port city in the south of Turkey, in the city's memory. For this purpose, in-depth face-to-face interviews were conducted with individuals in different age groups using Uray Street. The memories of Uray street were questioned by interviewing the users of long-term memory places in the area, and the changes that took place in the Uray street were questioned from the eyes of the owners of these places. The obtained memory data were evaluated and the changes were tried to be determined